2011
DOI: 10.1097/adm.0b013e3181d8dc62
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Adolescent Marijuana Use and Associated Psychosocial Characteristics

Abstract: Marijuana use in adolescents is associated with many adverse outcomes, including neurobiological and health consequences. Despite this, little is known about gender differences in the correlates of adolescent marijuana use. This study attempted to fill this gap by examining gender differences in the correlates of lifetime and past 30-day marijuana use. Data from a cross-sectional statewide survey of adolescent risk behavior participation in Connecticut were analyzed using chi-square and hierarchical logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 38 publications
9
93
1
2
Order By: Relevance
“…Because adolescent boys tend to report high levels of sensation seeking (d 'Acremont and Van der Linden, 2005;Cyders, 2013) -the most commonly researched impulsivity trait in adolescent marijuana use -and higher rates of marijuana use (Williams et al, 2007;Schepis et al, 2011), it is possible that the gender trends could be meaningful in more appropriately powered analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because adolescent boys tend to report high levels of sensation seeking (d 'Acremont and Van der Linden, 2005;Cyders, 2013) -the most commonly researched impulsivity trait in adolescent marijuana use -and higher rates of marijuana use (Williams et al, 2007;Schepis et al, 2011), it is possible that the gender trends could be meaningful in more appropriately powered analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Gender plays an important role in marijuana use behaviors (e.g., Ames et al, 2005;Kong et al, 2013) and impulsivity trait levels (d 'Acremont and Van der Linden, 2005;Cross et al, 2011;Cyders, 2013), such that adolescent boys tend to report higher levels of sensation seeking, positive urgency, and marijuana use (Williams et al, 2007;Schepis et al, 2011), although this gap is closing (see Johnson et al, 2015 for review). Adolescent boys begin using marijuana at an earlier age (Kosterman et al, 2000;Johnson et al, 2015) and are more likely to experience negative marijuana consequences (Ames et al, 2005).…”
Section: The Importance Of Gendermentioning
confidence: 99%
“…Emerging data support the promise of web-based substance use prevention for adolescents (Di Noia, Schwinn, Dastur, & Schinke, 2003; Duncan, Duncan, Beauchamp, Wells, & Ary, 2000; Gordon, 2000; Moore, Soderquist, & Werch, 2005; Newton, Teesson, Vogl, & Andrews, 2010; Newton, Vogl, Teesson, & Andrews, 2011; Schinke & Schwinn, 2005; Schwinn, Schinke, & Di Noia, 2010; Segal, Chen, Gordon, Kacir, & Gylys, 2003; Williams et al, 2005) and their parents (Gordon, 2000; Kacir, Gordon, & Kirby, 1999; Schinke, Schwinn, & Fang, 2010; Segal et al, 2003). The Internet enables users to overcome geographical limitations, enjoy flexible access to information, and have control over navigating program materials.…”
Section: Web-based Substance Use Prevention Programsmentioning
confidence: 98%
“…1 However, many studies have shown that male gender is also associated with a younger age of onset of schizophrenia. [2][3][4] Because males are more likely to use recreational drugs than females, 5,6 this raises the question of whether the earlier AOP in cannabis users could be confounded by gender.…”
Section: Introductionmentioning
confidence: 99%